2021
DOI: 10.1097/icl.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Structural Changes in Congenital Glaucoma

Abstract: To identify corneal structure differences on quantitative highfrequency ultrasound biomicroscopy (UBM) among subjects with congenital glaucoma compared with controls. Methods: This prospective case-control study evaluated 180 UBM images from 44 eyes of 30 subjects (18 control and 12 glaucoma, mean age 5.268.0 years, range 0.2-25.8 years) enrolled in the Pediatric Anterior Segment Imaging and Innovation Study (PASIIS). ImageJ was used to quantify a comprehensive set of corneal structures according to 21 quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Thus, the observed enlargement of the anterior chamber (indicating an increase in intraocular pressure) is likely due to an impairment of aqueous humor drainage through the malformed outflow structures in affected animals. High intraocular pressure accompanied by an enlargement of the ocular globe (known as buphthalmos) is a common manifestation of congenital glaucoma [ 50 ], one of the developmental phenotypes associated with mutations in FOXC1 . The mechanism of this disorder is not fully known; however, human studies identified developmental defects in the drainage structures of patients with congenital glaucoma caused by CYP1B1 mutations [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the observed enlargement of the anterior chamber (indicating an increase in intraocular pressure) is likely due to an impairment of aqueous humor drainage through the malformed outflow structures in affected animals. High intraocular pressure accompanied by an enlargement of the ocular globe (known as buphthalmos) is a common manifestation of congenital glaucoma [ 50 ], one of the developmental phenotypes associated with mutations in FOXC1 . The mechanism of this disorder is not fully known; however, human studies identified developmental defects in the drainage structures of patients with congenital glaucoma caused by CYP1B1 mutations [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… 54 In cases of buphthalmos, it may be more appropriate to continue with glasses, considering that the corneal diameter and keratometric values will change and the refractive error will decrease to lower values. 99 , 100 …”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic criteria encompass a positive IOP measurement over 21 mmHg, accompanied by certain structural alterations, such as a corneal diameter increase of more than 1.5 mm or an asymmetry of more than 1.5 mm. Furthermore, these characteristics encompass the concomitant occurrence of progressive myopia, accompanied by an augmentation in the corneal diameter and/or axial length of the ocular organ, an escalated excavation of the optical disk exceeding 20%, and the necessity for surgical intervention to regulate IOP 11,12 .…”
Section: Introductionmentioning
confidence: 99%